Separation of Powers Under the 1999 Nigerian Constitution: The Core Legal Dilemmas - Olusola Babatunde Adegbite; Oreoluwa Omotayo Oduniyi; Jubril Akinwunmi Farinde (Faculty of Law, Sriwijaya University, Indonesia, 2019)
At the core of Nigeria's constitutional practice lies the doctrine of separation of powers. The application of the principle is such that power under Nigeria's presidential cum federal system is delineated both horizontally and vertically. Even though the doctrine has a major feature of every constitution in the world, its implementation does not seem satisfactory given the insults that have been carried out by successive governments. This paper examines the doctrine of separation of powers and its complicatedness as regards to its practice in Nigeria's constitutional democracy. Reflecting on the history of Nigeria, this paper will discuss the eroded implementation of the principle of separation. As a result, it seems to be that the concept of